2012
DOI: 10.1186/1756-3305-5-119
|View full text |Cite
|
Sign up to set email alerts
|

The nutritional impacts of soil-transmitted helminths infections among Orang Asli schoolchildren in rural Malaysia

Abstract: BackgroundSoil-transmitted helminths (STH) infections, anaemia and malnutrition are major public health problems in school-age children in developing countries. This study was conducted on 289 Orang Asli (aboriginal) schoolchildren in order to assess the current prevalence and predictors of anaemia and malnutrition, as well as the nutritional impacts of STH infections among these children.MethodsA cross-sectional study was combined with a longitudinal follow-up three months after treatment with anthelminthic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
77
9
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(97 citation statements)
references
References 30 publications
8
77
9
3
Order By: Relevance
“…The main impact of STH infections is their association with malnutrition, vitamin A deficiency (VAD) and iron deficiency anaemia (IDA), which may have effects at the community level with regard to work and productivity in adults and growth, learning and school performance in children [2831]. As recommended by the WHO, vitamin A capsules and deworming tablets are distributed together by control programmes in many countries [11].…”
Section: Discussionmentioning
confidence: 99%
“…The main impact of STH infections is their association with malnutrition, vitamin A deficiency (VAD) and iron deficiency anaemia (IDA), which may have effects at the community level with regard to work and productivity in adults and growth, learning and school performance in children [2831]. As recommended by the WHO, vitamin A capsules and deworming tablets are distributed together by control programmes in many countries [11].…”
Section: Discussionmentioning
confidence: 99%
“…The estimated 200 children registered in the school were from the Temiar tribe. However, high absenteeism was common in schools located at Orang Asli settlements [11, 12]. …”
Section: Methodsmentioning
confidence: 99%
“…The places where children play are important for public health (9). In many studies, it has been demonstrated that parasitic infections have a considerable negative influence on health factors such as weight and height (10,11).…”
Section: Discussionmentioning
confidence: 99%